Risk factors for developmental quotients in ASD children: A cross-sectional study - Dong, Han-Yu; Miao, Chun-Yue; Zhang, Yu; Shan, Ling; Feng, Jun-Yan; Jia, Fei-Yong; Du, Lin (Frontiers in Psychology, 2023)
Objective To analyze the risk factors for developmental quotients (DQs) of children with autism spectrum disorder (ASD) and to better understand the effects of screen time on neurodevelopment in children with ASD. Methods We retrospectively analyzed the data of 382 children with ASD, including demographic profiles; socioeconomic status; score on the Chinese parent–child interaction scale (CPCIS); screen time questionnaire; ASD symptom rating scales, including the Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Autism Diagnostic Observation Schedule Second Edition (ADOS-2); and DQs using Griffiths Development Scales–Chinese Edition. Univariate analysis was carried out to analyze the factors related to the DQs of children with ASD, and then the linear regression model was used to identify the independent influencing factors of the DQs of children with ASD. Results Vitamin D (β = 0.180, p = 0.002), age (β = −0.283, p = 0.000) and CARS score (β = −0.347, p = 0.000) are risk factors related to DQ of locomotor in children with ASD. Vitamin D (β = 0.108, p = 0.034), CARS score (β = −0.503, p = 0.000), ADOS-2 severity score (β = −0.109, p = 0.045) and CPCIS score (β = 0.198, p = 0.000) are risk factors related to DQ of personal social skill in children with ASD. Vitamin D (β = 0.130, p = 0.018), CARS score (β = −0.469, p = 0.000), and CPCIS score (β = 0.133, p = 0.022) are risk factors related to DQ of hearing-speech in children with ASD. Vitamin D (β = 0.163, p = 0.003) and CARS score (β = −0.471, p = 0.000) are risk factors related to DQ of eye-hand coordination in children with ASD. Age (β = −0.140, p = 0.020), CARS score (β = −0.342, p = 0.000), ADOS-2 severity score (β = −0.133, p = 0.034) and CPCIS score (β = 0.193, p = 0.002) are risk factors related to DQ of performance in children with ASD. Vitamin D (β = 0.801, p = 0.000) and CPCIS score (β = 0.394, p = 0.019) are risk factors related to DQ of practical reasoning in children with ASD. Conclusion Vitamin D status, the severity of autistic symptoms and parent-child interaction are risk factors for developmental quotients in children with ASD. Screen exposure time is negatively associated with DQs in children with ASD but is not an independent risk factor for DQs.